2019
DOI: 10.1371/journal.pone.0224485
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the group tasks uncertainty model (MITAG) in a German sample

Abstract: Task uncertainty is a key factor in teamwork research. This study analyzed the psychometric characteristics of the Spanish Model of Group Tasks Uncertainty (MITAG) in two German samples. The participants (501 team members and 104 team leaders from a German research organization) answered the MITAG together with selected items from the German Job Diagnostic Survey (JDS) and the instrument Ambiguity facets of work (Ambiguitätsfacetten der Arbeit, AfA). Confirmatory factor analysis did not reproduce the original … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, the AVE of the EM_AT was 0.33, which indicated that about 67 percent of the variance of the EM_AT's items was due to the measurement error instead of be captured by the EM_AT itself (Fornell & Larcker, 1981). Since the unacceptable AVE of the EM_AT was 0.33, we may conclude that the convergent validity of the EM_AT was adequate based only on its CR of 0.745 (Fornell & Larcker, 1981;Malhotra, 2020; previous studies e.g., Leuteritz et al, 2019;Bittencourt et al, 2021).…”
Section: B) Phi Coefficient Of Inter-dimension Correlationmentioning
confidence: 77%
“…However, the AVE of the EM_AT was 0.33, which indicated that about 67 percent of the variance of the EM_AT's items was due to the measurement error instead of be captured by the EM_AT itself (Fornell & Larcker, 1981). Since the unacceptable AVE of the EM_AT was 0.33, we may conclude that the convergent validity of the EM_AT was adequate based only on its CR of 0.745 (Fornell & Larcker, 1981;Malhotra, 2020; previous studies e.g., Leuteritz et al, 2019;Bittencourt et al, 2021).…”
Section: B) Phi Coefficient Of Inter-dimension Correlationmentioning
confidence: 77%
“…According to Fornell and Larcker [ 78 ], discriminant validity is fulfilled when " each concept's AVE is greater than the squared correlation of the construct with any other construct ". Discriminant validity at item level is additional proved when MSV < AVE [ 79 ]. Therefore, it was explored whether the square root of the AVE of each variable was higher than the inter-factor correlations to test the discriminant validity [ 77 ].…”
Section: Methodsmentioning
confidence: 99%